154k views
1 vote
How do you answer this and please show work if you solve?

How do you answer this and please show work if you solve?-example-1
User BhavO
by
5.3k points

1 Answer

5 votes
To solve this, simply switch the X and y variables within one equation, and upon doing so, see and check if it equals to the other equation.

f(X) = -X + 4/5
Y = -X + 4/5
X = (-Y+4)/5
5X = -Y + 4
-Y = 5X - 4
Y = -5x + 4

Yes, by looking at the second equation it is an inverse of the first one.
User Umar Farooq
by
5.8k points